Mandapa (hall) of the Mandaleshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
View of the mandapa (hall) of the Mandaleshwar Mahadev Temple as seen from the mukhamandapa (front porch) of the temple. The mandapa is astylar, which means that it does not have any pillars in the centre of the hall. The pilasters are arranged along the sides to support the entire structure. The pilasters and pillar types are simple, plain shafts with minimal ornamentation of foliage motifs.